Antioxidant Activity of Methanol Extract from Several Indonesian Green Teas - simamora, adelina; Steven, Michael; Santoso, Adit Widodo; Rumiati, Flora; Timotius, Kris Herawan (Lembaga Penelitian Universitas YARSI, 2018)
As a common beverage, green tea is supposed to have beneficial health effect, such as antioxidant. At present, there are many green teas available in the market in Jakarta. Their quality, in their antioxidant activity, should be proved. This study aimed to investigate the antioxidant activity of extracts of green tea products commercially available in Jakarta. Four green tea samples from different factories (coded as A, B, C, and D) were selected and macerated using methanol. DPPH radical scavenging activity, reducing power ability and total antioxidant capacity were used to measure the antioxidant activity. The total phenolic content (TPC) was also determined. The studied green teas had varied TPC from 23.80 to 84.03 mG GAE/g extract, ranked as B > D > A > C. All samples exhibited various but strong antioxidant activity by DPPH assay, even better than standards ascorbic acid and butylated hydroxytoluene (BHT). However, all extracts showed similar activities in their reducing power ability and total antioxidant capacity, with activities less than standards. These findings confirm that the quality of the Indonesian commercial green teas were heterogeneous both in TPC or DPPH scavenging capacity. But, there is an indication that they are good as an antioxidant containing beverage.